Efficacy of selective digestive decontamination in patients with multiple myeloma undergoing high-dose chemotherapy and autologous stem cell transplantation. Issue 3 (23rd February 2019) - Mürner, Céline M.; Stenner-Liewen, Frank; Seifert, Burkhardt; Mueller, Nicolas J.; Schmidt, Adrian; Renner, Christoph; Schanz, Urs; Knuth, Alexander; Manz, Markus G.; Scharl, Michael; Gerber, Bernhard; Samaras, Panagiotis
Abstract: Selective digestive decontamination (SDD) with the oral, non-absorbable antimicrobial substances gentamicin, vancomycin and amphotericin B was optionally used at our institution to reduce the risk of gastrointestinal tract derived infections in multiple myeloma (MM) patients undergoing high-dose chemotherapy with subsequent autologous stem cell transplantation (HDCT/ASCT). The majority of patients received sulfamethoxazole-trimethoprim as pneumocystis pneumonia prophylaxis. From 203 patients receiving their first HDCT/ASCT between 2009 and 2015, we compared retrospectively 90 patients receiving SDD to 113 patients not receiving SDD. The administration of SDD was associated with a reduction of bacterial infections after HDCT/ASCT (overall: 8% versus 24%, p  = .002; gram-negative pathogens: 1% versus 11%, p  = .006) and less use of systemic antibiotics (62% versus 77%, p  = .022). Omission of SDD was an independent risk factor for developing neutropenic fever and bloodstream infections. SDD could be an option to reduce bacterial infections in patients undergoing HDCT/ASCT that needs to be tested in prospective trials.